2013
DOI: 10.1364/oe.21.023459
|View full text |Cite
|
Sign up to set email alerts
|

Energy shedding during nonlinear self-focusing of optical beams

Abstract: Self-focusing of intense laser beams and pulses of light in real nonlinear media is in general accompanied by material losses that require corrections to the conservative Nonlinear Schrödinger equations describing their propagation. Here we examine loss mechanisms that exist even in lossless media and are caused by shedding of energy away from the self-trapping beam making it to relax to an exact solution of lower energy. Using the conservative NLS equations with absorbing boundary conditions we show that ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For the case of spatio-temporal pulsed input we present results of the effects of the sign and magnitude of group velocity dispersion of the medium. We also describe the energy shedding that takes place during the self-focusing processes as the beam reshapes on entry to the medium and on propagation to a stable solitonic profile [3].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For the case of spatio-temporal pulsed input we present results of the effects of the sign and magnitude of group velocity dispersion of the medium. We also describe the energy shedding that takes place during the self-focusing processes as the beam reshapes on entry to the medium and on propagation to a stable solitonic profile [3].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…One especially relevant observation is the appearance of an annular structure around the main core of the self-trapped beam. In a recent study [11], it was shown that high-power self-trapped beams can shed energy away due to long-lived oscillations in amplitude and width, caused by periodic focusing and defocusing. This could explain the formation of the ring structure we observe in our experiments.…”
mentioning
confidence: 99%